Skriðuklaustur Monastery – 1550 Reconstruction - Kennedy, Sarah; Gunnarsson, Skúli; Cassidy, Catherine Anne; Oliver, Iain; Miller, Alan (Zenodo, 2020)
The Skriðuklaustur cloister was the last one to be founded during Iceland’s Catholic period, i.e. shortly before the country’s 16th-century Reformation. It was thus active for less than six decades, and could scarcely be said to have flourished for more than about four decades. The deed of gift is still preserved whereby the couple Sesselja Þorsteinsdóttir and the local sheriff Hallsteinn Þorsteinsson, who lived on the other side of this valley at Víðivellir ytri, donated Skriða farm as the site for a cloister. Although this deed was signed on 8 June 1500, it is considered certain that the cloister was founded sooner, probably in 1493 when Stefán Jónsson, bishop at Skálholt, came on his first visitation to this valley. A legend tells of a 15th-century miracle here in the valley of Fljótsdalur. As was often the case, the Valþjófsstaðir priest rode his horse along the valley in order to attend to a dying parishioner. When he arrived, he discovered that he had lost everything he needed for the last sacrament, Extreme Unction, so a farm boy was sent looking. Following the well-worn trail, he was passing below the farmhouses at Skriða when he noticed the wine chalice standing full of wine on a grassy hummock, with the paten over it holding the bread. This was considered to be a miracle which, according to the legend, was commemorated by building a chapel here, with its altar located where the hummock had been. Somewhat later, the cloister was founded here. Digitisation by Open Virtual Worlds, a research team within the School of Computer Science, University of St Andrews, in cooperation with the Gunnar Gunnarsson Institute at Skriðuklaustur and the National Museum of Iceland. Funded by the EU Northern Periphery and Arctic Programme 2014-2020 through the “Connected Culture and Natural Heritage in a Northern Environment” (CINE) project.